Biodegradable BBG/PCL composite scaffolds fabricated by selective laser sintering for directed regeneration of critical-sized bone defects. (January 2023) - Han, Jian; Wu, Jinzhe; Xiang, Xinjian; Xie, Lingxia; Chen, Ruiguo; Li, Ling; Ma, Kun; Sun, Qing; Yang, Runhuai; Huang, Tongling; Tong, Liping; Zhu, Lei; et al.
Graphical abstract: (a) Radius modeling of the rabbit model at different stages. (b) The schematic of the fabrication procedure for BBG/PCL rabbit radius scaffolds and their usage in the repair of critical-sized radius bone defects in rabbits. (c) Schematic diagram of bone regeneration mechanism on the BBG/PCL scaffold. Highlights: Borate bioactive glass/polycaprolactone (BBG/PCL) scaffolds are developed by SLS. The BBG/PCL scaffold with ∼70% porosity possesses adequate mechanical properties. The BBG/PCL scaffolds show satisfying degradation and protein adsorption behaviors. The BBG/PCL scaffolds exhibit excellent in vitro and in vivo biocompatibility. Customized BBG/PCL scaffold constructs promote osteogenesis and osseointegration. Abstract: The repair of critical-sized bone defects (CSBD) remains a significant challenge in clinical practice. Personalized 3D porous scaffolding is generally considered an ideal approach for directed regeneration of CSBD, which usually has irregular and complex 3D geometry. In this study, we designed a customized porous scaffold rabbit radius based on a body-centered cubic unit. Borate bioactive glass/polycaprolactone (BBG/PCL) composite scaffolds with different BBG contents (0%, 5%, 10%, 20%, and 40%) were fabricated using selective laser sintering. The pore geometry, porosity, mechanical strength, hydrophilicity, protein absorption, degradation behavior, in vitro cytocompatibility, and osteogenesis differentiation of the composite scaffolds were systematically characterized. The in vivo biological properties of the BBG/PCL composite scaffold for CSBD repair were assessed using a rabbit foreleg radius defect model. The results indicate that the BBG/PCL composite scaffold with 20% BBG content effectively promoted the proliferation of osteoblasts and repaired the rabbit radius defects. The mechanical strength of the scaffold was sufficient to maintain the integrity of the scaffold structure during a relatively long CSBD repair. Our results indicate that the BBG/PCL composite scaffold can be anticipated to be a promising biomaterial for CSBD repair.